2012
DOI: 10.14710/jitaa.37.3.213-219
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of 5-C Factors on Rate of Credit Return in Beef Cattle Farming in Central Java

Abstract: Tujuan penelitian adalah menganalisis (i) pendapatan usaha ternak sapi potong, (ii) kemampuan peternak untuk memenuhi kewajiban pengembalian kredit; (iii) peranan faktor Character, Capacity, Capital, Collateral dan Conditions (5C) dan pengaruhnya terhadap pengembalian kredit. Penelitian menggunakan metode survai pada peternak sapi potong pola penggemukan dan induk-anak yang memanfaatkan kredit sebagai modal usaha. Penentuan sampel menggunakan two stage clustered random sampling pada lima kabupaten berdasarkan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
3
1
Order By: Relevance
“…This result was 2.21 times higher than the results of the research of Priyanti et al (2012) (Huyen et al, 2010) after equalized. The income in this research was also 40.50% higher than the income of beef cattle fattening in the research of Prasetyo et al (2012) after equalized per bull during 1.5 months and the prevailing prices.…”
Section: Fattening Business Income On Optimum Durationcontrasting
confidence: 46%
See 2 more Smart Citations
“…This result was 2.21 times higher than the results of the research of Priyanti et al (2012) (Huyen et al, 2010) after equalized. The income in this research was also 40.50% higher than the income of beef cattle fattening in the research of Prasetyo et al (2012) after equalized per bull during 1.5 months and the prevailing prices.…”
Section: Fattening Business Income On Optimum Durationcontrasting
confidence: 46%
“…respectively IDR 25,385.45 and IDR 4,574.69. When the both income are equalized in 1.50 month, the income per kg of cattle body weight in this research is more higher than the income of the results of Prasetyo et al (2012), i.e. IDR 838.88 per kg of cattle body weight.…”
Section: Fattening Business Income On Optimum Durationmentioning
confidence: 63%
See 1 more Smart Citation
“…Even so, interviewed banks place character and capacity as the most important aspects in loan assessment as reported by Winarso (2015) and Wulandari et al (2017). While Prasetyo et al (2012) reported that capital and collateral are important in loan assessment: greater value of collateral and capital usually results in better repayment rates.…”
Section: Collateralmentioning
confidence: 99%